2016
DOI: 10.1007/978-3-319-28872-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Communication in Multi-robot Systems Using Directionality of Signal Strength

Abstract: Abstract-We consider the problem of satisfying communication demands in a multi-agent system where several robots cooperate on a task and a fixed subset of the agents act as mobile routers. Our goal is to position the team of robotic routers to provide communication coverage to the remaining client robots. We allow for dynamic environments and variable client demands, thus necessitating an adaptive solution. We present an innovative method that calculates a mapping between a robot's current position and the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…These blockages occur with positive and non-negligible probability as is modeled in [15]- [17] and they become more frequent as the distance between the transmitter and receiver grows. Connectivity is also a common problem in mobile robotic systems (see [18]- [21]), where robot location affects both the robot connectivity to the FC, and its event-detection probability. To the best of our knowledge, minimizing the expected loss function of cloud-cluster sensor networks where sensors are intermittently connected to the cloud was not previously investigated.…”
Section: A Related Workmentioning
confidence: 99%
“…These blockages occur with positive and non-negligible probability as is modeled in [15]- [17] and they become more frequent as the distance between the transmitter and receiver grows. Connectivity is also a common problem in mobile robotic systems (see [18]- [21]), where robot location affects both the robot connectivity to the FC, and its event-detection probability. To the best of our knowledge, minimizing the expected loss function of cloud-cluster sensor networks where sensors are intermittently connected to the cloud was not previously investigated.…”
Section: A Related Workmentioning
confidence: 99%
“…In order to establish reliable wireless communication with a team of client agents who are performing an independent task, Gil et al (2015) deployed an auxiliary team of robot routers. The idea is to find the best positions of the routers that support variable demanded rates to the client's robots.…”
Section: Communicationmentioning
confidence: 99%
“…In [32], the authors designed a comparative score, searching for a node message patterns that are dissimilar relative to the messages of other neighbors. In [33] the authors showed analytically and experimentally that it is possible to determine if messages come from the same source at the physical layer, providing a solution for the detection of Sybil-type attacks. In [22], [27] the authors proposed several strategies based on carefully crafted metrics for detecting and localizing attackers.…”
Section: Introductionmentioning
confidence: 99%